Letter from Dr. Carl D. Duncan to Patricia Whiting, Novemeber, 1964 - Duncan, Carl D. (Carl Dudley), 1895-1966:::Creator::::::::::::
Dr. Carl D. Duncan discusses events of the day and plans for future meetings with Patricia Whiting.